On going optical photometric monitoring of AGN TeV targets with the Watcher Robotic Telescope - Van Soelen, Brian (2015)
Active Galactic Nuclei (AGN) show variability on various time scales and present complex correlations between these variations at different wavelengths. Simultaneous multi-wavelength observations can therefore be used to place constraints on the different emission models. In May 2015 we began optical photometric monitoring of a subset of the known TeV emitting AGN using the Watcher Robotic Telescopes (Boyden Observatory, South Africa) to obtain long term photometric monitoring of these sources. Currently 17 targets are included in this monitoring campaign. The sources are observed once per night in the V, R & i’ bands, depending on observability and weather. The V, R and V-R light curves of four blazars are presented, all of which show variability which is consistent with previous studies. This demonstrates the feasibility of using the Watcher telescope to provide long term optical photometric monitoring of TeV blazars.